Eucholoeops Ameghino 1887 is the correct generic name of the basal megalonychid (mammalia, Xenarthra, Megatherioidea, Megalonychidae) sloth from the Santa Cruz Formation (late-early Miocene) of Patagonia, Argentina - Bargo, María Susana (2011)
There has been recent confusion over the generic name of the basal megalonychid (Gaudin, 2004) sloth Eucholoeops Ameghino, 1887, from the Santa Cruz Formation (Santacrucian Age; late Early Miocene, Santa Cruz Province, Argentina). At issue is the spelling of the third syllable of the name, either as Eucholoeops or Eucholaeops. As demonstrated here, the correct spelling is Eucholoeops.Eucholoeops Ameghino, 1887, from the Santa Cruz Formation (Santacrucian Age; late Early Miocene, Santa Cruz Province, Argentina). At issue is the spelling of the third syllable of the name, either as Eucholoeops or Eucholaeops. As demonstrated here, the correct spelling is Eucholoeops.